INTEGRASI KECERDASAN BUATAN DALAM PEMBELAJARAN PAI DI ERA DIGITAL - dani, Rahmadani; Rahmadani, Rahmadani; Annisa, Khusnia Nur; Barokah, Najla; Riadi, Akhmad (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The term "intelligence" in Latin, known as "intelligo", means "I understand". Basically, intelligence refers to the ability to understand and engage in an action. In general, intelligence can also be defined as something created or produced by humans, be it something naturally occurring or man-made. This review is based on a literature review that includes an in-depth analysis of. Diverse sources of information, including scientific journals, books, and relevant articles. AI was first published in 1956 at Dartmouth College. AI has evolved since then thanks to various studies on its underlying theories and principles. Although the term AI did not exist until 1956, theories related to AI have been around since 1941. The integration of artificial intelligence in Islamic Religious Education (PAI) learning in the digital age brings benefits in increasing learning effectiveness by personalizing the learning experience for students.